Reflexos da pandemia nas famílias de crianças/adolescentes com transtorno do espectro autista - Santos, Bruna (Universidade Federal de São Carlos, 2023)
In the face of the Covid-19 pandemic, parents and relatives of children with Autism Spectrum Disorder are more likely to experience psychic suffering as a result of isolation measures, financial issues, interruption of services and physical and mental overload. In this direction, the objective of the present study was to identify what has been produced in the scientific literature about the implications of the COVID-19 pandemic for families of children and adolescents with ASD, based on an integrative literature review. The results reinforce the psychological impacts for families of children and adolescents with ASD during the pandemic, the lack of interventions aimed at preventing this suffering and cooperating in the creation of coping strategies. It is evident, therefore, the indispensability of building means of support for families and strategies that meet the psychosocial needs of this population.
Reflections of the pandemic on the families of children/adolescents with autism spectrum disorder
Keywords: Covid-19; Família; Autismo; Family; Autism; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL